Synthesis of Hydroxyapatite from Precipitated Calcium Carbonate of Thorny Shells (Murex trapa) with Variable Ca/P Mole Ratio and pH - Prayoga, Ferdiyan Tri; Aprilianty, Syasmitha Lucky; Edahwati, Luluk (Jurnal Rekayasa Kimia & Lingkungan, 2024)
Hydroxyapatite, with the chemical formula Ca10(PO4)6(OH)2, is a mineral found in human bones and teeth, providing density and strength to bones as it is a major component of the bone matrix. It is widely used in biomedicine for bone implants, dental fillings, and hard tissue replacement. Hydroxyapatite can be produced from materials high in CaCO3, such as cattle bones, seashells, and fish bones. In this research, thorny clam shells (Murex trapa), with a CaCO3 content of 91.08%, were used. Precipitated Calcium Carbonate (PCC) was formed using the carbonation method, while hydroxyapatite synthesis was performed using the precipitation method. Variables during synthesis included Ca/P molar ratios of 1.47, 1.67, and 1.87, and pH levels of 7, 9, and 11. The best result was achieved at a Ca/P molar ratio of 1.67 and pH 9, with a yield of 96%. The hydroxyapatite was analyzed using Fourier Transform Infra-Red, revealing the core groups PO43-, CO32-, and OH-.Scanning Electron Microscopy-Energy Dispersive X-Ray analysis showed the hydroxyapatite had a crystalline structure, tending to be spherical and agglomerated.